Great earthquakes and tsunamis of the past 2000 years at the Salmon River estuary, central Oregon coast, USA - Nelson, A. R.; Asquith, A. C.; Grants, W. C. (Bulletin of the Seismological Society of America, 2004)
Four buried tidal marsh soils at a protected inlet near the mouth of the Salmon River yield definitive to equivocal evidence for coseismic subsidence and burial by tsunami-deposited sand during great earthquakes at the Cascadia subduction zone. An extensive, landward-tapering sheet of sand overlies a peaty tidal-marsh soil over much of the lower estuary. Limited pollen and macrofossil data suggest that the soil suddenly subsided 0.3-1.0 m shortly before burial. Regional correlation of similar soils at tens of estuaries to the north and south and precise C-14 ages from one Salmon River site imply that the youngest soil subsided during the great earthquake of 26 January A.D. 1700. Evidence for sudden subsidence of three older soils during great earthquakes is more equivocal because older-soil stratigraphy can be explained by local hydrographic changes in the estuary. Regional C-14 correlation of two of the three older soils with soils at sites that better meet criteria for a great-earthquake origin is consistent with the older soils recording subsidence and tsunamis during at least two great earthquakes. Pollen evidence of sudden coseismic subsidence from the older soils is inconclusive, probably because the amount of subsidence was small (<0.5 m). The shallow depths of the older soils yield rates of relative sea-level rise substantially less than rates previously calculated for Oregon estuaries.
855anTimes Cited:18Cited References Count:80